MARSIADAPARI SEBAGAI PRAKTIK SOLIDARITAS DAN GOTONG ROYONG MASYARAKAT BATAK TOBA DI TENGAH TANTANGAN ZAMAN - Albertus Agung Dwi Kristiyanto (Jurnal Humaniora & Sosial Sains, 2025)
The focus of this research is to analyze the relevance of the Marsiadapari tradition as local wisdom of the Toba Batak in the context of modern challenges. This tradition can be integrated with new technology-based cultures. Using Armada Riyanto's intersubjective metaphysical approach, marsiadapari is understood as a relational practice that emphasizes equality, responsibility, and solidarity between humans. The marsiadapari tradition is no longer limited to an agrarian context, but has undergone changes into new forms such as social solidarity, economic cooperation, nomadic communities, and digital collaboration. The method used in this research is a literature study with a qualitative approach. This research has obtained results that the values ​​contained in the marsiadapari tradition remain relevant in facing the challenges of modern individualism, especially when technology tends to create social isolation. The integration of marsiadapari with digital culture opens new spaces for broader and more inclusive relationships, while maintaining the communal identity of the Toba Batak people.